Impact of Unplanned Excision on Prognosis of Patients with Extremity Soft Tissue Sarcoma. (30th April 2013) - Umer, Hafiz Muhammad; Umer, Masood; Qadir, Irfan; Abbasi, Nadeem; Masood, Nehal
Abstract : Unplanned excision of soft tissue sarcomas (STSs) outside comprehensive tumor management centers necessitates the need for wide reexcision to achieve adequate margins. We retrospectively reviewed medical records of 135 patients with STS operated at our hospital with the goal of examining outcomes, in terms of local recurrence (LR) and metastasis rate (MR), of reexcision following unplanned excision of STS and comparing results with those of first-time planned surgery. Eighty-four patients had their first-time surgery and 51 patients had come to us following unplanned excision at prereferral hospital. Mean age of all patients was 41.8 ± 21.9 years. The LR and MR was 14.3% and 8.3%, respectively, in patients undergoing first resection, whereas it was 21.4% and 13.7%, respectively, in patients undergoing revision surgery. Average duration from previous unplanned excision was 8 months. Twelve patients were referred immediately after excised specimen revealed STS, while 39 patients presented after evident local recurrence. Wide reexcision was attempted in 48 patients while three patients need amputation. Adjuvant radiotherapy was administered in all patients undergoing limb-sparing surgery. Ten patients needed adjuvant chemotherapy. We conclude that wide reexcision of STS has poorer outcomes compared to planned excision. Therefore, patients with soft tissue masses should be managed by multidisciplinary oncology team at specialized cancer centers.